Haemostasis in normal pregnancy: a balancing act?. (1st April 2005) - Holmes, V.A.; Wallace, J.M.W.
Abstract : Pregnancy is a risk factor for venous thrombosis and the incidence of venous thromboembolism during normal pregnancy is 6-fold higher during pregnancy than in the general female population of child-bearing age. This incidence is, however, remarkably low given the increases in markers of haemostatic activation observed during normal pregnancy. During normal healthy pregnancy there are substantial changes in the haemostatic system, many of which are procoagulant and supposed to be in preparation for the haemostatic challenge of delivery. Normal haemostasis requires a balance between coagulation and fibrinolysis to maintain the integrity of the vasculature, and complex physiological changes are evident during pregnancy which appear to ensure a constant coagulation/fibrinolysis balance. This balance is maintained, at least partly, by an increase in fibrinolytic activity, but decreases in other factors such as factor XI and monocyte tissue factor expression may also serve to counterbalance procoagulant changes.